Penyuluhan dan Pemberian Obat Cacing Sebagai Upaya Pencegahan Kecacingan Bagi Siswa Kelas IV/A di UPT SPF SD Negeri Pannara - Tamzil Azizi Musdar; Nurfiddin Farid; Hilmiati Wahid (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
Intestinal diseases caused by transmission from worms as a source of helminthiasis generally occur in areas with subtropical and tropical climate conditions which have a wet climate and lack of awareness among the public regarding maintaining health and sanitation of the surrounding environment. Around 60 percent of Indonesians experience worm infections. The largest age group is 5-14 years old. The prevalence figure is 60 percent, 21 percent of which attack elementary school age children. This disease can be spread by eggs in human waste found in soil and water, therefore awareness of clean and sanitary living is very influential, the process or pattern of feces disposal is also very influential in the spread of this worm. The high rate of soil contamination by Ascaris, which reaches >70%, can also be caused by feces that are thrown anywhere, such as in bushes or around houses close to where you live. Preventing recurrent infections is very important by practicing clean and healthy living habits such as avoiding contact with soil that may be contaminated with human feces, washing hands with soap and water before handling food, protecting food from soil and washing or heating food that falls on the floor. Several researchers have shown that school age is a group that is often affected by worm infections because they are often in contact with soil. Apart from the government, the role of teachers and parents is very important in providing understanding or knowledge about worms so that they are more disciplined. The aim of community service is to provide knowledge and understanding to class IV/A students at SD N Pannara regarding the dangers of worms and how to prevent them and administer worm medicine.